Diseño e Implementación de un Sistema IoT para la Monitorización de la Variabilidad de la Frecuencia Cardiaca (2023)
The project focused on developing a heart rate variability (HRV) monitoring system using Internet of Things (IoT) technologies. Using an Arduino Nano 33 IoT, electrocardiographic signals were acquired and processed in real time, ensuring data security through the MQTT protocol. The information transmission was carried out to the cloud through the ThingSpeak platform, where a dashboard was implemented to display heart rate (HR) and HRV metrics, such as PRR50 and RMSSD.